Design of an Archival Information System for LLDIKTI Region VIII using the Research and Development Method - Pamungkas, Dionisius Adi Prabu; Rahardja, Yani (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The LLDIKTI Region VIII office is an institution responsible for facilitating and supervising higher education institutions in the Bali and Nusa Tenggara regions, particularly through the UK3 unit in managing archives. Currently, the archival management at the LLDIKTI Region VIII office relies solely on the centralized Electronic Official Document Information System (SINDE) provided by the government, without any local system to support independent backup and digitalization of records. This creates issues when there are disruptions in access to the central system or when more flexible, localized archive management is required. Therefore, there is a need for technology that enables local backup and the digitalization of physical documents into digital formats. This study adopts the Research and Development (R&D) method, emphasizing a balance between theory, design, and implementation based on user needs, existing problems, and user preferences. The result of this study is the design of a web-based User Interface (UI) and User Experience (UX) for the Digital Archive Center Information System of LLDIKTI Region VIII (PADI8). System usability testing was conducted using the System Usability Scale (SUS) method with five respondents, consisting of UK3 archival staff (3 women and 2 men). Data were collected through interviews and direct observation of system usage. The SUS scores were 83.7 from the admin perspective and 83 from the general user perspective. Based on the SUS interpretation criteria, the system falls into Grade A, with an adjective rating of “excellent” and an acceptability range of “acceptable,” indicating a high level of user satisfaction. This system is expected to improve the office’s efficiency, security, and autonomy in digital archive management and serve as an initial step toward sustainable digital transformation within the LLDIKTI Region VIII environment.